Platelet-rich plasma in combination with bovine derived xenograft in the treatment of generalized aggressive periodontitis: A case report with re-entry - (:unkn) unknown (TAYLOR & FRANCIS INC, 2007)
Prominence has been given recently to the use of platelet-rich plasma (PRP) in combination with bone graft materials for predictably obtaining periodontal regeneration through bioengineering. The purpose of this report was to present clinical, radiographic and re-entry results of a generalized aggressive periodontitis (GAP) patient with wide intrabony periodontal defects treated with combined PRP and bovine derived xenograft (BDX). A-32 year old GAP patient who received non-surgical therapy and had 12 intrabony defects was treated with PRP and BDX combination. Prior to surgery and at 12 months, probing depth, marginal recession, relative attachment, probing bone and radiographic bone levels were measured. Re-entry was additionally performed at 12 months. Clinical and radiographic measurements together with re-entry results showed marked improvements from baseline with increased stabilization of whole dentition including the hopeless teeth. The surgical technique together with the materials used may be a possible solution for extensive bone loss.
Keywords: periodontal regeneration; intrabony defects; aggressive periodontitis; platelet-rich plasma; bovine derived xenograft; GUIDED TISSUE REGENERATION; CELLS IN-VITRO; INTRABONY DEFECTS; GROWTH-FACTOR; CLINICAL-TRIAL; BONE; HUMANS; LIGAMENT; THERAPY